Tools and Techniques for Financial Stability Analysis - Ramlall, Indranarain (Theory and Practice of Financial Stability Ser., 2018)
Tools and Techniques for Financial Stability Analysis explores all key aspects of analytical tools and challenges for sound financial stability assessments. Comprehensive coverage is given to value at risk, stress testing, graphical tools for financial stability, the financial system stress index, as well as ratios and metrics.